2006
DOI: 10.1074/jbc.m507862200
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Formate-lyase and a Novel Route of Eukaryotic ATP Synthesis in Chlamydomonas Mitochondria

Abstract: Pyruvate formate-lyase (PFL) catalyzes the non-oxidative conversion of pyruvate to formate and acetyl-CoA. PFL and its activating enzyme (PFL-AE) are common among strict anaerobic and microaerophilic prokaryotes but are very rare among eukaryotes. In a proteome survey of isolated Chlamydomonas reinhardtii mitochondria, we found several PFL-specific peptides leading to the identification of cDNAs for PFL and PFL-AE, establishing the existence of a PFL system in this photosynthetic algae. Anaerobiosis and darkne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
166
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(176 citation statements)
references
References 46 publications
(59 reference statements)
8
166
1
1
Order By: Relevance
“…Respective distributions of PSAD and ATPase (Fig. 6, B and C) indicate that chloroplasts were efficiently separated from mitochondria, although some unavoidable cross contamination was observed (26,42). Interestingly, the signal detected by the Nda2 antibody (Fig.…”
Section: Six C Reinhardtii Genes Encode For Putative Type Ii Nadhmentioning
confidence: 99%
“…Respective distributions of PSAD and ATPase (Fig. 6, B and C) indicate that chloroplasts were efficiently separated from mitochondria, although some unavoidable cross contamination was observed (26,42). Interestingly, the signal detected by the Nda2 antibody (Fig.…”
Section: Six C Reinhardtii Genes Encode For Putative Type Ii Nadhmentioning
confidence: 99%
“…In the Enterobacteriaceae, the AdhE enzyme represents the major route for recycling NADH during fermentation (Clark and Cronan, 1980;Leonardo et al, 1996), as highlighted by the inability of an E. coli adhE mutant to grow on minimal medium under anoxic conditions (Cunningham and Clark, 1986;Gupta and Clark, 1989). Interestingly, an AdhE/ADH1 homolog is not present in the majority of prokaryotes, and among the eukaryotes, it has only been identified in a few amitochondriate protists and some green algae (Atteia et al, 2003(Atteia et al, , 2006. In the alga Polytomella, the ADHE protein was localized to the mitochondrion (Atteia et al, 2003), while in Chlamydomonas, ADH1 was found to be present in chloroplasts (Terashima et al, 2010).…”
mentioning
confidence: 99%
“…A number of these fermentation pathways are typical of those present in various prokaryotes and some eukaryotes (Mus et al, 2007). Some enzymes that function in these pathways include pyruvate:ferredoxin oxidoreductase (PFR), pyruvate decarboxylase (PDC), lactate dehydrogenase (LDH), pyruvate formate lyase (PFL), alcohol dehydrogenase (ADH), phosphate acetyltransferase (PAT), acetate kinase (ACK), and the two [FeFe] hydrogenases (HYDA1 and HYDA2) and their maturation proteins, HYDG and HYDEF (Posewitz et al, 2004;Atteia et al, 2006;Ghirardi et al, 2007;Mus et al, 2007;Hemschemeier et al, 2008;Grossman et al, 2011). The anaerobic activities of these and other enzymes result in the secretion of organic acids (formate, lactate, malate, acetate, and succinate) and alcohols (ethanol and glycerol) as well as the evolution of H 2 and CO 2 (Gfeller and Gibbs, 1984;Kreuzberg, 1984;Ohta et al, 1987;Tsygankov et al, 2002;Kosourov et al, 2003;Mus et al, 2007;Dubini et al, 2009).…”
mentioning
confidence: 99%
“…It is known for some time that in absence of oxygen, green algae such as Chlamydomonas and Chlorella have the ability to produce organic acids (acetate, formate, lactate, and succinate), alcohols (ethanol), and gases (CO 2 and H 2 ) (6 -9). The genome sequences of Chlamydomonas reinhardtii (10) and Chlorella variabilis NC64 (11) have greatly helped to get a good grasp of the anaerobic pathways in the two algae (12)(13)(14). Since then, in C. reinhardtii, these pathways have been actively investigated through molecular and biochemical studies of the fermentative enzymes (15)(16)(17)(18)(19), as well as physiological studies of mutant strains (20 -25).…”
mentioning
confidence: 99%